Water, Sanitation, and Hygiene Service Availability at Rural Health Care Facilities in Southwestern Uganda - Mulogo, Edgar Mugema; Matte, Micheal; Wesuta, Andrew; Bagenda, Fred; Apecu, Richard; Ntaro, Moses (Journal of Environmental and Public Health, 2018)
There is a paucity of information on the state of water, sanitation, and hygiene (WASH) at health care facilities in Uganda. A survey on WASH service availability was conducted at 50 health care facilities across 4 districts of rural southwestern Uganda between September and November 2015. *e main water points at the majority (94%) of the health care facilities were improved sources, while improved toilets were available at 96% of the health care facilities visited. Hospitals had the poorest toilet to patient ratio (1: 63). Only 38% of the health care facilities had hand washing facilities at the toilets. *e lack of hand washing facilities was most prominent at the level IV health centre toilets (71%). Hand washing facilities were available at other points within most (76%) of the health care facilities. However, both water and soap were present at only 24% of these health care facilities. *e poor toilet to patient/caregiver ratios particularly in the high volume health care facilities calls for the provision of cheaper options for improved sanitation in these settings. Priority should also be given to the sustainable provision of hygiene amenities such as soap for hand washing particularly the high patient volume health care facilities, in this case the level IV health centers and hospitals.
Keywords: Water; Sanitation; Hygiene; Service; Health Care Facilities; Uganda